Pickering Emulsions Electrostatically Stabilized by Cellulose Nanocrystals - Varanasi, Swambabu; Henzel, Leeav; Mendoza, Llyza; Prathapan, Ragesh; Batchelor, Warren; Tabor, Rico; Garnier, Gil (Frontiers in Chemistry, 2018)
Cellulose Nanocrystals (CNC) are explored to stabilize oil/water emulsions for their ability to adsorb at the oil/water interface. In this work, the role of electrostatics forces in the CNC ability to stabilize oil/water emulsions is explored using canola oil/water and hexadecane/water as model systems. Canola oil/water and Hexadecane/ water (20/80, v/v) emulsions were stabilised with the addition of CNCs using ultrasonication. Emulsion droplet sizes range from 1 to 4µm as measured by optical microscopy. It is found that CNC can stabilize oil/water emulsions regardless of their charge density. However, reducing the surface charge density, by adding salts and varying pH, can reduce the amount of CNC required to form a stable emulsion. Adding 3mM Na+ or 1mM or lower Ca+2 to a CNC suspension reduces by 30% the amount of CNC required to stabilized 2mL of Canola oil. On the other hand, adding salt increases the emulsion volume. The addition of 100mM Na+ or the reduction of pH below 2 leads to the aggregation of CNC; emulsions formed under these conditions showed gel like behaviour. This work shows the potential of nanocellulose crystal in stabilizing food and industrial emulsions. This is of interest for applications where biodegradability, biocompatibility and food grade requirements are needed.